Penerapan Model Ekspository Dengan Menggunakan Metode Demontrasi Dan Pemberian Tugas Untuk Meningkatkan Prestasi Belajar - I Nyoman Mulyadi (Jayapangus Press, 2020)
The problem formulation of this research is the Application of Expository Model with Demonstration Method and Giving Assignments to improve mathematics learning achievement of students of class IXC semester I of SMP Negeri 3 Selat, 2016/2017 school year. The purpose of this study was to improve mathematics learning achievement of students of class IXC of SMP Negeri 3 Selat in the first semester, 2016/2017 school year. The place for this class action research is at SMP Negeri 3 Selat, by taking the research subjects of class IXC students in the first semester of 2016/2017 school year. The object of this class action research is an increase in Mathematics learning achievement of students of class IXC Middle School 3 Strait, 2016/2017 academic year. The initial average value of 69.83 rose to 74.67 in the first cycle and in the second cycle rose to 75.64. The expository model with demonstration and assignment methods is very effective to be applied in the learning process that results in active, enthusiastic, critical thinking students and can understand the material being taught so that students' learning achievement increases.